"Não é fácil viver no coletivo". Experiência e consciência de classe no assentamento Conquista na Fronteira em Dionísio Cerqueira/SC (1988-2013) - Schwingel, Kassiane (2014)
The Assentamento Conquista da Fronteira is the great object of research and analysis of this work. Such settlement was established in the year of 1988, in the city of Dionísio Cerqueira-SC, by two corporate of agriculturists: one, deriving from Movimento dos Sem Terra and the other, made up by families of it's own city. This experience justifies itself by the need of knowing differentiated purposals of relations of work and humans, as well as the result of this specific organization that can be a mirror for other groups. This work seeks for knowing the agrarian reality of the catarinense west since the decade of 1950, as well as understanding how were the experiences on the settlements that arised on the region in the decade of 1980. From this, it is possible to make an analysis about what the Assentamento Conquista da Fronteira represents today and which are your characteristics that are result of the story of the settlers, as members of a movement of struggle for land. This discussion becomes valid and important, because it allows recognizing how a concrete experience of agrarian reforming organizes itself, in addition to exposing the importance of simbolic elements. For the study concretion, field researches were performed on the settlement, searches at Centro de Memória Oeste Catarinense, apart from interviews with the members of the Assentamento. With this, it was possible to relate the story according to their point of view, besides from doing observations about the rotine on the place. Based on concepts of Thompson and Gramsci, it was possible to realize the importance of the common experiences as unifying element, apart from the value given to the formation of a class consciousness. In this sense, stands out the local leadership, performing a organic intellectual function, besides from the entities linked to catholic church who had given meaning to the strife through the constant spiritual work. Having understood what it is and how this experience is organized, the work looks for relating it to the concepts of passive revolution and popular revolution, in order to enhance even more this analysis